Penerapan Nilai Tradisi Dalam Adat Perkawinan Masyarakat Samin di Era Globalisasi - Yuniar Pramestya Wardhani; Sarmini Sarmini (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Traditional values are passed down across generations and serve as life guidance. In the Samin community of Dusun Jepang, Bojonegoro, these values are preserved in marriage customs, particularly through the jawab and paseksen ceremonies. This study aims to describe the application of these traditional values and analyze their sustainability amidst globalization. Using a descriptive qualitative method and a case study approach, data were collected through observation and in-depth interviews and analyzed with the Miles and Huberman model.Findings show that the core ceremonies remain unchanged, while adaptations such as dowries, receptions, and formal registration have emerged. These changes reflect the community’s ability to balance tradition and modernization while upholding core values such as honesty, simplicity, and communal harmony.